Method for producing electrode for secondary battery using nonaqueous electrolyte, binder for secondary battery electrode using nonaqueous electrolyte, binder for secondary battery electrode, composition for producing electrode, electrode mixture, and electrode

By using powder binder without active substances composed of polytetrafluoroethylene resin and conductive additives, and using spray drying and shear processing methods, the PTFE electrode binder has been solved by increasing resistance and insufficient strength due to PTFE electrode binder. The problem is that low resistance value and high strength electrode manufacturing is achieved.

CN119487648APending Publication Date: 2025-02-18DAIKIN INDUSTRIES LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202380050103.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-30
Filing Date
2023-06-22
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

When using PTFE as the electrode binder in the prior art, the electrode resistance value is easily increased and the strength is insufficient.

Method used

The electrode mixture is prepared by spray drying and shearing treatment. The content of the polytetrafluoroethylene resin is preferably 1.8 mass % The moisture content is 1000 ppm or less.

Benefits of technology

It effectively reduces the resistance value of the electrode, and at the same time increases the strength of the electrode, solving the problems of high resistance and insufficient strength of the electrode.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005211382450000251
    Figure BDA0005211382450000251
Patent Text Reader

Abstract

Provided are: a method for producing an electrode for a secondary battery, which is capable of reducing the resistance value of an electrode using PTFE and has excellent strength; and a binder. A method for producing an electrode for a secondary battery using a non-aqueous electrolyte solution, said method being characterized by comprising: a step (1) for preparing a powder-containing composition for producing an electrode by using a binder that is a powder containing no active material and comprising a composition containing a polytetrafluoroethylene resin and a conductive auxiliary agent as essential components; and a step (2) for obtaining an electrode mixture by applying a shear force while mixing the composition for electrode production, the step (2) being performed under the condition that the solvent content of the composition for electrode production is 10 mass% or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for producing an electrode for a secondary battery using a non-aqueous electrolyte, a binder for a secondary battery electrode using a non-aqueous electrolyte, a binder for a secondary battery electrode, a composition for producing an electrode, an electrode mixture and an electrode. Background Art

[0002] The use of fibrillated polytetrafluoroethylene (PTFE) as a binder in an electrode of a lithium ion battery containing a non-aqueous electrolyte is under investigation (Patent Document 1).

[0003] Furthermore, it is disclosed that a uniform mixed powder obtained by mixing a conductive material and PTFE by spray drying is obtained (Patent Documents 2 to 4).

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application No. 2017-517862

[0007] Patent Document 2: Japanese Patent Application Laid-Open No. 6-316784

[0008] Patent Document 3: Japanese Patent Application Publication No. 2008-140809

[0009] Patent Document 4: International Publication No. 2020 / 170797

[0010] Patent Document 5: Japanese Patent Application Publication No. 2020-115485 Summary of the invention

[0011] Problems to be solved by the invention

[0012] The present invention can provide a method for producing an electrode for a secondary battery and a binder that can reduce the resistance value of an electrode using PTFE and has excellent strength.

[0013] Means for solving problems

[0014] The present invention is a method for manufacturing an electrode for a secondary battery using a non-aqueous electrolyte, characterized in that it comprises: step (1), using a binder composed of a composition having polytetrafluoroethylene resin and a conductive auxiliary agent as essential components and being a powder without an active material, to prepare a composition for preparing an electrode as a powder; and step (2), mixing the composition for preparing an electrode while applying a shear force to obtain an electrode mixture, wherein the step (2) is performed under the condition that the amount of solvent contained in the composition for preparing an electrode is 10% by mass or less. The content of polytetrafluoroethylene resin in the electrode mixture is preferably 1.8% by mass or less.

[0015] The binder preferably has a water content of 1000 ppm or less.

[0016] The above-mentioned binder is preferably produced by a production method having a step (A) of mixing a polytetrafluoroethylene resin and a conductive auxiliary agent in the presence of a liquid medium.

[0017] The above-mentioned liquid medium is preferably water.

[0018] The above-mentioned binder is preferably obtained by a production method having a step (B) of drying the composition obtained in the step (A) by spray drying.

[0019] The polytetrafluoroethylene resin preferably has a standard specific gravity of 2.130 to 2.200.

[0020] The electrode-forming composition preferably contains a positive electrode active material.

[0021] The secondary battery is preferably a lithium ion secondary battery.

[0022] The polytetrafluoroethylene resin preferably has a fibrous structure in which the fibril diameter (median value) in the secondary battery electrode is 150 nm or less.

[0023] The binder preferably has an element ratio of fluorine to carbon (F / C ratio) of 0.4 to 3.0 as measured by elemental analysis.

[0024] The present invention is also a binder for secondary battery electrodes using a non-aqueous electrolyte, characterized in that it is composed of a composition having polytetrafluoroethylene resin and a conductive aid as essential components, and is a powder that does not contain an electrode active substance, and contains polytetrafluoroethylene resin and a conductive aid in a weight ratio of 90:10 to 65:35.

[0025] The binder for secondary battery electrodes preferably has a water content of 1000 ppm or less.

[0026] The binder for secondary battery electrodes preferably has an element ratio of fluorine to carbon (F / C ratio) of 0.4 to 3.0 as measured by elemental analysis.

[0027] The present invention is also a binder for secondary battery electrodes using a non-aqueous electrolyte, comprising a mixed powder of a polytetrafluoroethylene resin and Ketjen black and / or carbon nanotubes.

[0028] The present invention is also a composition for producing an electrode, characterized in that it contains the above-mentioned binder for secondary battery electrodes.

[0029] The present invention is also an electrode mixture, characterized in that it contains the above-mentioned binder for secondary battery electrodes.

[0030] The present invention is also an electrode, characterized in that it comprises the above-mentioned electrode mixture.

[0031] Effects of the Invention

[0032] The present invention can provide a method for producing an electrode for a secondary battery and a binder that can reduce the resistance value of an electrode using PTFE and has excellent strength. DETAILED DESCRIPTION

[0033] The present invention is described in detail below.

[0034] The electrode mixture using PTFE as a binder may have a high resistance value of the electrode. The present invention provides a method for producing an electrode, which solves such a problem and can obtain an electrode with a low resistance value.

[0035] In the electrode mixture using PTFE as a binder, the PTFE is fibrillated to thereby function as a binder.

[0036] But, when PTFE and conductive aid are mixed with the form of powder respectively to manufacture electrode, electrode high resistance is changed sometimes.It is inferred that this is because PTFE does not fully form conductive path because of its inhomogeneous existence in electrode.And then, if the inhomogeneous existence of composition is produced in electrode, then also becomes the reason of the intensity reduction of electrode.On the other hand, when mixing violently in order to eliminate inhomogeneous existence, the fibrillation of PTFE excessively occurs, produces the reduction of flexibility, intensity.Therefore, by using the binding agent that can not produce the inhomogeneous existence of PTFE and conductive aid, such problem can be solved.

[0037] The method for manufacturing an electrode for a secondary battery using a non-aqueous electrolyte of the present invention is characterized in that a binder having a polytetrafluoroethylene resin and a conductive auxiliary agent as essential components and being a powder without an active material is used. It should be noted that it will be referred to as the first binder of the present invention below. Hereinafter, such a binder and the components mixed in the binder are described in detail.

[0038] On the other hand, it is known that if PTFE is mixed with a conductive aid in advance, lithium is eluted from the active material due to moisture in a liquid medium, and the active material deteriorates, thereby causing problems such as reduced battery capacity and increased battery resistance (Patent Document 5). Therefore, by using a binder that does not contain an active material and is composed of a composition having PTFE and a conductive aid as essential components, the purpose of the present invention can be achieved without being limited by the active material.

[0039] In addition, when a mixed powder of polytetrafluoroethylene resin and Ketjen black or carbon nanotubes is used as a binder, it is preferred in terms of being able to reduce electrode resistance, and the use of the above mixed powder binder can also achieve the purpose of the present invention. This effect is an effect that cannot be obtained when other carbon-based conductive additives such as acetylene black are used. Such a binder is recorded as the second binder of the present invention.

[0040] The method for manufacturing the first secondary battery electrode using a non-aqueous electrolyte of the present invention is characterized in that a binder is used which is a composition having PTFE and a conductive aid as essential components and is a powder containing no active material. That is, the particles constituting the powder are not composed of only PTFE and a conductive aid, but are composed of a composition containing both PTFE and a conductive aid.

[0041] Hereinafter, such a binder and components blended in the binder will be described in detail.

[0042] (polytetrafluoroethylene resin)

[0043] In the present invention, the PTFE is not particularly limited and may be a homopolymer or a fibrillating copolymer, but a homopolymer is more preferred.

[0044] In the case of a copolymer, examples of the fluorine-containing monomer as a comonomer include chlorotrifluoroethylene, hexafluoropropylene, fluoroalkylethylene, perfluoroalkylethylene, fluoroalkyl / fluorovinyl ether and the like.

[0045] The standard specific gravity (SSG) of the PTFE powder used as a raw material when preparing the mixture of the present invention is 2.200 or less. By setting the SSG within the above range, the electrode strength can also be improved.

[0046] The SSG is preferably 2.180 or less, more preferably 2.170 or less, further preferably 2.160 or less, further more preferably 2.150 or less, further more preferably 2.145 or less, and particularly preferably 2.140 or less.

[0047] In addition, the above-mentioned SSG is preferably 2.130 or more.

[0048] Standard specific gravity [SSG] is the specific gravity of a sample prepared in accordance with ASTM D-4895-89 and measured by the water displacement method.

[0049] The PTFE used in the present invention can have a core-shell structure. As the PTFE with a core-shell structure, for example, the PTFE of the shell of the core and the lower PTFE or modified PTFE of the PTFE of high molecular weight in the particle can be enumerated. As such PTFE, for example, the PTFE recorded in writing in the Japanese Patent Table 2005-527652 communique can be enumerated.

[0050] The PTFE in powder form satisfying the above parameters can be obtained by a conventional production method, for example, by the production methods described in International Publication No. 2015-080291, International Publication No. 2012-086710, etc.

[0051] (Conductive additive)

[0052] As the above-mentioned conductive auxiliary agent, known conductive materials can be used arbitrarily. As specific examples, metal materials such as copper and nickel, graphite (graphite) such as natural graphite and artificial graphite, carbon black such as acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, needle coke, carbon nanotubes, carbon nanohorns, carbon nanofibers, fullerenes and graphene, carbon materials such as amorphous carbon such as VGCF, etc. can be cited. Ketjen black, acetylene black, and carbon nanotubes are particularly preferred. Among carbon nanotubes, multilayer carbon nanotubes are preferred. It should be noted that they can be used alone or in any combination and ratio. Examples of commercially available carbon black include TOKABLACK #4300, #4400, #4500, #5500, etc. (manufactured by Tokai Carbon Co., Ltd., furnace black), Printex L, etc. (manufactured by Degussa, furnace black), Raven 7000, 5750, 5250, 5000 ULTRA III, 5000 ULTRA, etc., Conductex SC ULTRA, Conductex 975 ULTRA, etc., PUERBLACK 100, 115, 205, etc. (manufactured by Columbia, furnace black), #2350, #2400B, #2600B, #30050B, #3030B, #3230B, #3350B, #3400B, #5400B, etc. (manufactured by Mitsubishi Chemical Corporation, furnace black), MONARCH 1400, 1300, 900, Vulcan XC-72R, Black Pearls2000, LITX-50, LITX-200, etc. (manufactured by Cabot, furnace black), Ensaco 250G, Ensaco260G, Ensaco 350G, Super-P Li (manufactured by IMERYS, furnace black), Ketjen Black ECP, ECP-600JD, LIONITECB, etc. (manufactured by Lion Specialty Chemicals, Ketjen Black), Denka Black HS-100, Li-100, FX-35 (manufactured by Denka Co., Ltd., acetylene black), etc. As commercially available VGCF, VGCF-H (manufactured by Showa Denko Co., Ltd.) and the like can be cited. As commercially available multilayer carbon nanotubes, FT7000 (manufactured by CNano Co., Ltd.) and the like can be cited. As multilayer carbon nanotubes, the average outer diameter is preferably 4nm to 20nm, and more preferably 6nm to 12nm. The average fiber length is preferably 1μm to 30μm, and more preferably 3μm to 20μm. Thereby, good conductivity can be obtained.

[0053] When producing the electrode sheet, a conductive auxiliary agent may be further added and mixed for use.

[0054] The binder of the present invention preferably contains the conductive additive in a ratio of 1.0 to 60.0 mass relative to the total amount of the binder. Thus, good conductivity and electrode strength can be obtained. The lower limit is more preferably 1.5 or more, and more preferably 2.0 or more. The upper limit is more preferably 55.0 or more, and more preferably 50.0 or less.

[0055] It should be noted that, in the present invention, the conductive auxiliary agent must be contained in the binder, but when the electrode sheet is produced using the electrode mixture, PTFE and the conductive auxiliary agent may be further mixed and used.

[0056] The conductive aid is preferably used in an amount of 0.1% by mass or more, preferably 0.5% by mass or more, more preferably 0.8% by mass or more, and usually 50% by mass or less, preferably 30% by mass or less, more preferably 15% by mass or less in the electrode mixture. If the content is below this range, the conductivity is sometimes insufficient. On the contrary, if the content is above this range, the battery capacity is sometimes reduced.

[0057] When mixing the conductive auxiliary agent and PTFE, materials that can be added as needed include conductive materials, dispersants, thickeners, etc. For example, celluloses such as carboxymethyl cellulose (CMC) and methyl cellulose (MC) can be preferably used as thickeners.

[0058] When using components other than these conductive additives and PTFE, the blending amount of such components is preferably 5.0 mass % or less relative to the total amount of the binder. If more than 5.0 mass % of the above other components are blended, the purpose of the present invention may not be fully achieved.

[0059] (Binder)

[0060] The binder used in the present invention is a binder in which a composition having PTFE and a conductive aid as essential components is in a powdered form. That is, a composition in which PTFE and a conductive aid are mixed is in a powdered form, and a mixture of powders of PTFE powder and conductive aid powder is not included. Such a state is not particularly limited, and particles in a state of granulation by spray drying are particularly preferred.

[0061] The binder preferably contains PTFE and the conductive additive at a weight ratio of 99:1 to 50:50. Among the above mixing ratios, the weight ratio is preferably 95:5 to 60:40, and more preferably 90:10 to 65:35.

[0062] The manufacturing method of the above-mentioned binder is not particularly limited and can be manufactured by any method, wherein it is preferably manufactured by a manufacturing method having a step (A) of mixing PTFE and a conductive aid in the presence of a liquid medium. In this case, a method of adding a conductive aid as a powder to a liquid dispersion of PTFE and mixing, a method of mixing a liquid dispersion of PTFE with a liquid dispersion of a conductive aid, etc. can be enumerated.

[0063] The mixing method may be a general method, for example, a dispersing machine, a homomixer, a mixer such as a planetary mixer, a homogenizer, a wet jet mill, etc., but the invention is not limited thereto.

[0064] In the above step (A), a dispersion having PTFE, a conductive aid and a liquid medium as essential components is used. In such a dispersion, the total amount of PTFE and the conductive aid is preferably 1 wt % to 60 wt % relative to the total amount of PTFE, the conductive aid and the liquid medium. The above lower limit is more preferably 2 wt % or more, and further preferably 3 wt % or more. The above upper limit is more preferably 50 wt % or less, and further preferably 30 wt % or less.

[0065] Mixing them in a liquid medium is preferred because PTFE and the conductive additive can be mixed with high uniformity. The liquid medium in such mixing is preferably water.

[0066] In this case, it is preferable to use an aqueous dispersion of PTFE obtained by emulsion polymerization as the raw material.

[0067] From the aspect of obtaining an electrode composite sheet with higher strength and excellent homogeneity, the average primary particle size of the PTFE used as the raw material of the binder is preferably 100nm to 350nm. By making the average primary particle size within the above range, the molecular weight of the PTFE is high, and the bonding force and flexibility of the electrode are improved.

[0068] The above-mentioned average primary particle size is more preferably 340 nm or less, further preferably 330 nm or less, further more preferably 300 nm or less, further more preferably 280 nm or less, particularly preferably 250 nm or less, and more preferably 150 nm or more, further preferably 170 nm or more, further more preferably 200 nm or more.

[0069] The average primary particle size is measured by the following method.

[0070] The PTFE aqueous dispersion was diluted with water to a solid content concentration of 0.15% by mass, and the transmittance of the projected light at 550 nm relative to the unit length of the obtained diluted emulsion and the number-based length average particle size determined by orientation measurement using a transmission electron microscope photograph were measured to prepare a calibration curve. The number average particle size was determined from the measured transmittance of the projected light at 550 nm of each sample using this calibration curve as the average primary particle size.

[0071] The mixture of PTFE and the conductive aid mixed in the liquid medium by the above-mentioned step (A) is preferably then dried by spray drying (step (B)) to remove the liquid medium. Drying methods include, for example, a rack dryer, a vacuum dryer, a freeze dryer, a hot air dryer, a drum dryer, a spray dryer, etc. Spray drying is particularly preferred. Spray drying is a method of spraying a mixture of a liquid and a solid into a gas to rapidly dry it and produce a dry powder.

[0072] Thus, a powdery binder in which PTFE and a conductive aid are uniformly mixed can be obtained. Spray drying is a generally known method and can be carried out in a usual manner using any known device. The above-mentioned step (B) can be carried out by a general method using a known general device. The drying temperature is preferably in the range of, for example, 100°C to 250°C. When it is above 100°C, the solvent can be fully removed, and when it is below 250°C, the energy consumption can be further reduced, which is preferred. The drying temperature is more preferably above 110°C, and more preferably below 220°C. In addition, the amount of liquid supplied also depends on the scale of production, for example, it can be in the range of 0.1L / hour to 2L / hour. In addition, the nozzle size for spraying the solution also depends on the scale of production, for example, it can be in the range of 0.5mm to 5mm in diameter.

[0073] The water content of the binder obtained in this way is preferably 1000 ppm or less.

[0074] By adjusting the water content to 1000 ppm or less, it is preferable from the viewpoint of being able to produce a secondary battery with less gas generation as an initial characteristic.

[0075] The water content is more preferably 500 ppm or less.

[0076] [Determination of water content]

[0077] Regarding the moisture content of the binder, a Karl Fischer moisture meter (ADP-511 / MKC-510N manufactured by Kyoto Electronics Industry Co., Ltd.) with a boat-type moisture vaporizer was used, and the vaporized moisture was measured by heating the moisture vaporizer to 210°C. As a carrier gas, nitrogen was circulated at a flow rate of 200 mL / min, and the measurement time was set to 30 minutes. In addition, Chem-Aqua was used as a Karl Fischer reagent. The sample amount was set to 1.5 g.

[0078] The second binder of the present invention is a mixed powder of polytetrafluoroethylene resin and Ketjen black and / or carbon nanotubes. When such a mixed powder is used as a binder, it is preferable to use a known carbon conductive additive such as acetylene black in terms of reducing electrode resistance and improving battery characteristics, and can be used in the same manner as the first binder.

[0079] In the second binder, the Ketjen black and / or carbon nanotubes used are not particularly limited, and the above-mentioned materials can be used. Furthermore, the carbon nanotubes are preferably multi-layered, and more specifically, preferably have an average fiber length of 1 μm to 20 μm.

[0080] The polytetrafluoroethylene used in the second binder may be the same as that used in the first binder.

[0081] The second binder may be obtained through the steps (A) and (B) in the same manner as the first binder, or may be obtained by simply mixing these components.

[0082] In the electrode-forming composition and the like described in detail below, the first binder and the second binder can be used in the same manner.

[0083] (Electrode preparation composition)

[0084] The composition for electrode preparation refers to a composition containing all the components necessary for the electrode. That is, it refers to a composition in which other electrode components such as an electrode active material are mixed in the above-mentioned binder. The composition for electrode preparation is a composition containing an electrode active material, an additional conductive auxiliary agent, etc. in addition to the above-mentioned binder.

[0085] (Electrode Active Material)

[0086] As the above-mentioned positive electrode active material, there is no particular restriction as long as it can electrochemically encapsulate and release alkali metal ions. For example, it is preferably a material containing an alkali metal and at least one transition metal. As specific examples, transition metal composite oxides containing alkali metals, transition metal phosphate compounds containing alkali metals, conductive polymers, etc. can be cited.

[0087] Among them, as the positive electrode active material, a transition metal composite oxide containing an alkali metal that can generate a high voltage is particularly preferred. As the above-mentioned alkali metal ion, lithium ion, sodium ion, potassium ion, etc. can be cited. In a preferred embodiment, the alkali metal ion can be a lithium ion. That is, in this embodiment, the alkali metal ion secondary battery is a lithium ion secondary battery.

[0088] Examples of the alkali metal-containing transition metal composite oxide include

[0089] Formula: M a Mn 2-b M 1 b O 4

[0090] (wherein, M is at least one metal selected from the group consisting of Li, Na and K; 0.9≤a; 0≤b≤1.5; M 1 an alkali metal-manganese spinel composite oxide represented by at least one metal selected from the group consisting of Fe, Co, Ni, Cu, Zn, Al, Sn, Cr, V, Ti, Mg, Ca, Sr, B, Ga, In, Si and Ge,

[0091] Formula: MNi 1-c M 2 cO 2

[0092] (wherein, M is at least one metal selected from the group consisting of Li, Na and K; 0≤c≤0.5; M 2 an alkali metal-nickel composite oxide represented by at least one metal selected from the group consisting of Fe, Co, Mn, Cu, Zn, Al, Sn, Cr, V, Ti, Mg, Ca, Sr, B, Ga, In, Si and Ge, or

[0093] Formula: MCo 1-d M 3 d O 2

[0094] (wherein, M is at least one metal selected from the group consisting of Li, Na and K; 0≤d≤0.5; M 3 The alkali metal-cobalt composite oxide is represented by at least one metal selected from the group consisting of Fe, Ni, Mn, Cu, Zn, Al, Sn, Cr, V, Ti, Mg, Ca, Sr, B, Ga, In, Si and Ge.

[0095] Among the above, M is preferably one metal selected from the group consisting of Li, Na and K, more preferably Li or Na, and further preferably Li.

[0096] Among them, MCoO is preferred from the perspective of providing a secondary battery with high energy density and high output. 2 MMnO 2 、MNiO 2 MMn 2 O 4 、MNi 0.8 Co 0.15 Al 0.05 O 2 , or MNi 1 / 3 Co 1 / 3 Mn 1 / 3 O 2 etc., and preferably the compound represented by the following general formula (3).

[0097] MNi h Co i Mn j M 5 k O 2 (3)

[0098] (wherein, M is at least one metal selected from the group consisting of Li, Na and K, M 5 represents at least one selected from the group consisting of Fe, Cu, Zn, Al, Sn, Cr, V, Ti, Mg, Ca, Sr, B, Ga, In, Si and Ge, (h+i+j+k)=1.0, 0≤h≤1.0, 0≤i≤1.0, 0≤j≤1.5, 0≤k≤0.2.)

[0099] Examples of the alkali metal-containing transition metal phosphate compound include the following formula (4):

[0100] M e M 4 f (PO 4 ) g (4)

[0101] (wherein, M is at least one metal selected from the group consisting of Li, Na and K, M 4 It represents at least one selected from the group consisting of V, Ti, Cr, Mn, Fe, Co, Ni and Cu, and a compound represented by 0.5≤e≤3, 1≤f≤2, and 1≤g≤3).

[0102] Among the above, M is preferably one metal selected from the group consisting of Li, Na and K, more preferably Li or Na, and further preferably Li.

[0103] As the transition metal of the lithium-containing transition metal phosphate compound, V, Ti, Cr, Mn, Fe, Co, Ni, Cu, etc. are preferred. As specific examples, LiFePO 4 , Li 3 Fe 2 (PO 4 ) 3 、LiFeP 2 O 7 Iron phosphates such as LiCoPO 4 Cobalt phosphates, etc.; substances obtained by replacing part of the transition metal atoms serving as the main body of these lithium transition metal phosphate compounds with other metals such as Al, Ti, V, Cr, Mn, Fe, Co, Li, Ni, Cu, Zn, Mg, Ga, Zr, Nb, Si, etc.

[0104] The lithium-containing transition metal phosphate compound preferably has an olivine structure.

[0105] As other positive electrode active materials, MFePO can be cited. 4 、MNi 0.8 Co 0.2 O 2 、M 1.2 Fe 0.4 Mn 0.4 O 2 、MNi 0.5 Mn 1.5 O 2 , MV 3 O 6 、M 2 MnO 3 (wherein, M is at least one metal selected from the group consisting of Li, Na and K). In particular, M 2 MnO 3 、MNi 0.5 Mn 1.5 O 2 When the positive electrode active material is operated at a voltage exceeding 4.4V or a voltage above 4.6V, the crystal structure will not collapse, which is preferred from this aspect. Therefore, even if the electrochemical device such as the secondary battery using the positive electrode material including the positive electrode active material exemplified above is stored at high temperature, the residual capacity is not easy to decrease, the resistance increase rate is not easy to change, and even if it is operated at a high voltage, the battery performance will not deteriorate, so it is preferred.

[0106] Other positive electrode active materials include M 2 MnO 3 and MM 6 O 2(wherein, M is at least one metal selected from the group consisting of Li, Na, and K, and M 6 is a transition metal such as Co, Ni, Mn, Fe, etc.) a solid solution material, etc.

[0107] As the above-mentioned solid solution material, for example, it is a general formula M x [Mn (1-y) M 7 y O z shown alkali metal manganese oxide. Here, M in the formula is at least one metal selected from the group consisting of Li, Na, and K, and M 7 is composed of at least one metal element other than M and Mn, and for example, contains one or more elements selected from the group consisting of Co, Ni, Fe, Ti, Mo, W, Cr, Zr, and Sn. In addition, the values of x, y, and z in the formula are in the range of 1 < x < 2, 0 ≤ y < 1, and 1.5 < z < 3. Among them, Li 1.2 Mn 0.5 Co 0.14 Ni 0.14 O 2 such as Li 2 MnO 3 based and solid-solution containing LiNiO 2 , LiCoO 2 manganese-containing solid solution materials can provide alkali metal ion secondary batteries with high energy density and are preferred in this regard.

[0108] In addition, if the positive electrode active material contains lithium phosphate, the continuous charging characteristics are improved, so it is preferred. The use of lithium phosphate is not limited, and it is preferred to use a mixture of the above-mentioned positive electrode active material and lithium phosphate. The amount of lithium phosphate used is preferably 0.1% by mass or more, more preferably 0.3% by mass or more, further preferably 0.5% by mass or more, based on the total lower limit of the above-mentioned positive electrode active material and lithium phosphate, and the upper limit is preferably 10% by mass or less, more preferably 8% by mass or less, further preferably 5% by mass or less.

[0109] As the above-mentioned conductive polymer, p-doped conductive polymers and n-doped conductive polymers can be cited. As conductive polymers, polyacetylene-based, polystyrene-based, heterocyclic polymers, ionic polymers, ladder and network polymers, etc. can be cited.

[0110] In addition, a substance having a different composition from that of the positive electrode active material may be attached to the surface of the positive electrode active material, and the positive electrode active material obtained thereby may be used. Examples of the surface-attached substance include oxides such as aluminum oxide, silicon oxide, titanium oxide, zirconium oxide, magnesium oxide, calcium oxide, boron oxide, antimony oxide, and bismuth oxide; sulfates such as lithium sulfate, sodium sulfate, potassium sulfate, magnesium sulfate, calcium sulfate, and aluminum sulfate; carbonates such as lithium carbonate, calcium carbonate, and magnesium carbonate; carbon; and the like.

[0111] These surface-attached substances can be attached to the surface of the positive electrode active material by, for example, the following methods: dissolving or suspending in a solvent, impregnating or adding to the positive electrode active material and drying; dissolving or suspending the surface-attached substance precursor in a solvent, impregnating or adding to the positive electrode active material, and then reacting it by heating or the like; adding to the positive electrode active material precursor and simultaneously firing; etc. It should be noted that in the case of attaching carbon, a method of attaching the carbon material in the form of, for example, activated carbon and then mechanically attaching it can also be adopted.

[0112] The amount of the surface-attached substance is preferably 0.1 ppm or more, more preferably 1 ppm or more, and further preferably 10 ppm or more, as a lower limit, and preferably 20% or less, more preferably 10% or less, and further preferably 5% or less, relative to the above-mentioned positive electrode active material, as an upper limit. The surface-attached substance can inhibit the oxidation reaction of the electrolyte on the surface of the positive electrode active material, and can improve the battery life. If the amount of attachment is too small, the effect cannot be fully demonstrated; if the amount of attachment is too large, it will hinder the entry and exit of lithium ions, so the resistance may increase.

[0113] The shape of the particles of the positive electrode active material may be a block shape, a polyhedron shape, a sphere shape, an ellipsoidal sphere shape, a plate shape, a needle shape, a column shape, etc. The primary particles may be aggregated to form secondary particles.

[0114] The tap density of the positive electrode active material is preferably 0.5 g / cm 3 More preferably, 0.8 g / cm 3 More preferably, 1.0 g / cm 3Above. If the tap density of the positive electrode active material is less than the above lower limit, the amount of conductive material and binder required when the positive electrode active material layer is formed will increase, and sometimes the filling rate of the positive electrode active material in the positive electrode active material layer will be limited, and the battery capacity will be limited. By using a composite oxide powder with a high tap density, a high-density positive electrode active material layer can be formed. The larger the tap density is, the better, and there is no particular upper limit. However, if it is too large, the diffusion of lithium ions in the positive electrode active material layer with the electrolyte as the medium becomes rate-limiting, and sometimes the load characteristics are easily reduced. Therefore, the upper limit is preferably 4.0g / cm 3 Below, more preferably 3.7 g / cm 3 Below, more preferably 3.5 g / cm 3 the following.

[0115] It should be noted that in the present invention, the tap density is the powder packing density (tap density) g / cm2 when 5 g to 10 g of the positive electrode active material powder is placed in a 10 ml glass measuring cylinder and vibrated 200 times with a stroke of about 20 mm. 3 Find out.

[0116] The median diameter d50 of the particles of the positive electrode active material (secondary particle diameter in the case where the primary particles agglomerate to form secondary particles) is preferably 0.3 μm or more, more preferably 0.5 μm or more, further preferably 0.8 μm or more, most preferably 1.0 μm or more, and preferably 30 μm or less, more preferably 27 μm or less, further preferably 25 μm or less, and most preferably 22 μm or less. If it is less than the above lower limit, a high tap density product may not be obtained; if it exceeds the upper limit, the diffusion of lithium in the particles takes time, so there will be problems such as reduced battery performance. Here, by mixing two or more of the above-mentioned positive electrode active materials with different median diameters d50, the filling property during positive electrode production can be further improved.

[0117] It should be noted that, in the present invention, median diameter d50 is measured using known laser diffraction / scattering particle size distribution measuring device. When using LA-920 manufactured by HORIBA as a particle size distribution meter, as the dispersion medium used during measurement, 0.1% by mass sodium hexametaphosphate aqueous solution is used, and after 5 minutes of ultrasonic dispersion, the refractive index is set to 1.24 for measurement.

[0118] In the case where the primary particles are condensed to form secondary particles, the average primary particle size of the positive electrode active material is preferably 0.05 μm or more, more preferably 0.1 μm or more, and further preferably 0.2 μm or more, and the upper limit is preferably 5 μm or less, more preferably 4 μm or less, further preferably 3 μm or less, and most preferably 2 μm or less. If the upper limit is exceeded, it is difficult to form spherical secondary particles, which has an adverse effect on the powder filling property, or the specific surface area is greatly reduced, so the possibility of reduced battery performance such as output characteristics is sometimes increased. On the contrary, if it is lower than the lower limit, crystallization is usually not developed, so problems such as poor reversibility of charge and discharge may occur.

[0119] It should be noted that, in the present invention, the average primary particle size is measured by observation using a scanning electron microscope (SEM). Specifically, in a photograph of a magnification of 10,000 times, for any 50 primary particles, the longest value of the slice intercepted by the left and right boundaries of the primary particles on a straight line in the horizontal direction is obtained, and the average value is taken to obtain the primary particle size.

[0120] The BET specific surface area of ​​the positive electrode active material is preferably 0.1 m 2 / g or more, more preferably 0.2m 2 / g or more, more preferably 0.3m 2 / g or more, and the upper limit is preferably 50m 2 / g or less, more preferably 40m 2 / g or less, more preferably 30m 2 If the BET specific surface area is smaller than this range, the battery performance is likely to be reduced; if the BET specific surface area is larger than this range, it may be difficult to increase the tap density.

[0121] It should be noted that, in the present invention, the BET specific surface area is defined as follows: using a surface area meter (for example, a fully automatic surface area measuring device manufactured by Okura Riken Co., Ltd.), the sample is pre-dried at 150°C for 30 minutes under nitrogen flow, and then a nitrogen-helium mixed gas accurately adjusted to a relative pressure value of 0.3 relative to atmospheric pressure is used to measure the sample by the nitrogen adsorption BET single-point method based on the gas flow method, and the obtained value is used to define the BET specific surface area.

[0122] When the secondary battery of the present invention is used as a large lithium ion secondary battery for hybrid vehicles or distributed power sources, high output is required, so the particles of the positive electrode active material preferably mainly contain secondary particles.

[0123] The particles of the positive electrode active material preferably have an average particle size of 40 μm or less for the secondary particles, and contain 0.5% by volume to 7.0% by volume of microparticles having an average primary particle size of 1 μm or less. By containing microparticles having an average primary particle size of 1 μm or less, the contact area with the electrolyte becomes larger, which can further accelerate the diffusion of lithium ions between the electrode mixture and the electrolyte, and as a result, the output performance of the battery can be improved.

[0124] As a method for producing the positive electrode active material, a common method for producing an inorganic compound is used. In particular, various methods are considered for producing a spherical or ellipsoidal active material, for example, the following method can be cited: dissolving or crushing a transition metal raw material in a solvent such as water, adjusting the pH under stirring, producing a spherical precursor and recovering it, drying it as needed, and then adding LiOH, Li 2 CO 3 、LiNO 3 The active material is obtained by sintering at high temperature.

[0125] In order to manufacture the positive electrode, the positive electrode active material may be used alone, or two or more of different compositions may be used together in any combination or ratio. As a preferred combination in this case, LiCoO 2 With LiNi 0.33 Co 0.33 Mn 0.33 O 2 The combination of ternary systems, LiCoO 2 With LiMn 2 O 4 or a combination of materials in which a portion of the Mn is replaced by other transition metals or the like, or LiFePO 4 With LiCoO 2 Or a combination of substances in which a part of Co is replaced by other transition metals or the like.

[0126] From the viewpoint of increasing the battery capacity, the content of the positive electrode active material in the positive electrode mixture is preferably 50% by mass to 99.5% by mass, and more preferably 80% by mass to 99% by mass.

[0127] In addition, the content of the positive electrode active material is preferably 80% by mass or more, more preferably 82% by mass or more, and particularly preferably 84% by mass or more. In addition, the upper limit is preferably 99% by mass or less, more preferably 98% by mass or less. If the content of the positive electrode active material in the positive electrode mixture is low, the capacitance is sometimes insufficient. On the contrary, if the content is too high, the strength of the positive electrode is sometimes insufficient.

[0128] The negative electrode active material is not particularly limited, and examples thereof include materials selected from lithium metal, artificial graphite, graphite carbon fiber, resin-fired carbon, pyrolysis vapor-grown carbon, coke, mesocarbon microbeads (MCMB), furfuryl alcohol resin-fired carbon, polyacene, pitch-based carbon fiber, vapor-grown carbon fiber, natural graphite, and carbon containing carbonaceous materials such as non-graphitizable carbon, silicon-containing compounds such as silicon and silicon alloys, Li 4 Ti 5 O 12 Among them, a substance containing at least a part of a carbonaceous material or a silicon-containing compound can be particularly preferably used.

[0129] The negative electrode active material used in the present invention preferably contains silicon as a constituent element. By containing silicon as a constituent element, a high-capacity battery can be produced.

[0130] As the material containing silicon, silicon particles, particles having a structure in which silicon particles are dispersed in a silicon-based compound, silicon oxide particles represented by the general formula SiOx (0.5≤x≤1.6), or mixtures thereof are preferred. By using these substances, a negative electrode mixture for a lithium ion secondary battery having higher initial charge and discharge efficiency, high capacity, and excellent cycle characteristics is obtained.

[0131] Silicon oxide in the present invention is a general term for amorphous silicon oxides, and silicon oxide before disproportionation is represented by the general formula SiOx (0.5≤x≤1.6). x is preferably 0.8≤x<1.6, and more preferably 0.8≤x<1.3. The silicon oxide can be obtained, for example, by heating a mixture of silicon dioxide and metallic silicon and cooling and precipitating the generated silicon monoxide gas.

[0132] Particles having a structure in which silicon microparticles are dispersed in a silicon-based compound can be obtained, for example, as follows: a method in which silicon microparticles are mixed with a silicon-based compound and the mixture is fired; or silicon oxide particles before disproportionation represented by the general formula SiOx are heat-treated in an inactive, non-oxidizing atmosphere such as argon at a temperature of 400°C or more, preferably 800°C to 1,100°C, to perform a disproportionation reaction, thereby obtaining. In particular, the material obtained by the latter method is preferred because the silicon microcrystals are uniformly dispersed. The above-mentioned disproportionation reaction can make the size of silicon nanoparticles 1nm to 100nm. It should be noted that the silicon oxide in the particles having a structure in which silicon nanoparticles are dispersed in silicon oxide is preferably silicon dioxide. It should be noted that the silicon nanoparticles (crystals) dispersed in the amorphous silicon oxide can be confirmed by transmission electron microscopy.

[0133] The physical properties of the particles containing silicon can be appropriately selected according to the target composite particles. For example, the average particle size is preferably 0.1 μm to 50 μm, and the lower limit is more preferably 0.2 μm or more, and further preferably 0.5 μm or more. The upper limit is more preferably 30 μm or less, and further preferably 20 μm or less. It should be noted that the average particle size in the present invention is represented by the weight average particle size in the particle size distribution measurement based on the laser diffraction method.

[0134] The BET specific surface area of ​​the particles containing silicon is preferably 0.5 m 2 / g~100m 2 / g, more preferably 1m 2 / g~20m 2 / g. If the BET specific surface area is 0.5m 2 / g or more, there is no possibility of reduced adhesion when applied to the electrode and reduced battery characteristics. 2 / g or less, the proportion of silicon dioxide on the particle surface becomes large, and the battery capacity does not decrease when used as a negative electrode material for a lithium ion secondary battery.

[0135] By coating the silicon-containing particles with carbon to impart conductivity, it is observed that the battery characteristics are improved. As a method for imparting conductivity, there can be cited a method of mixing with conductive particles such as graphite, a method of coating the surface of the silicon-containing particles with a carbon coating, and a method of combining the two. The method of coating with a carbon coating is preferred, and as a coating method, a chemical vapor deposition (CVD) method is more preferred.

[0136] In order to increase the capacity of the obtained electrode mixture, the content of the above-mentioned negative electrode active material is preferably more than 40 mass %, more preferably more than 50 mass %, and particularly preferably more than 60 mass % in the electrode mixture. In addition, the upper limit is preferably below 99 mass %, more preferably below 98 mass %.

[0137] (Other ingredients)

[0138] The electrode composition may further include a thermoplastic resin. Examples of the thermoplastic resin include vinylidene fluoride, polypropylene, polyethylene, polystyrene, polyethylene terephthalate, and polyoxyethylene. One may be used alone, or two or more may be used in any combination and ratio.

[0139] Thermoplastic resin is generally more than 0.01 mass %, preferably more than 0.05 mass %, more preferably more than 0.10 mass %, and generally below 3.0 mass %, preferably below 2.5 mass %, more preferably below 2.0 mass %.By adding thermoplastic resin, the mechanical strength of electrode can be improved.In addition, if it exceeds this scope, the ratio of electrode active material in electrode mixture is reduced, and sometimes the problem of the capacity reduction of battery or the problem of resistance increase between active material can be produced.

[0140] (Method for manufacturing electrode)

[0141] The manufacturing method of the electrode of the present invention preferably uses the electrode preparation composition obtained by mixing the above-mentioned components, and forms it into sheets. In the sheeting, in order to save the drying process, it is preferably carried out by reducing the amount of liquid medium or not using liquid medium at all, not preparing slurry and applying shear stress to the electrode preparation composition as a powder. In addition, in order to reduce the load of the device, a solvent can also be added in small amounts as a lubricant. The solvent is preferably an organic solvent, and as the amount of solvent contained, relative to the electrode preparation composition, it is preferably 10% by mass or less, more preferably 5% by mass or less, and further preferably 3% by mass or less. As the lower limit of the above-mentioned amount of solvent contained, it is not particularly limited, and is preferably 0.5% by mass or more.

[0142] As the solvent, for example, N-methyl-2-pyrrolidone, butyl butyrate, acetone, etc., which dissolve the thermoplastic resin in the electrode mixture, can be cited. In addition, carbonates, ether compounds, and ionic liquids that can be used as components in the electrolyte can be cited. In particular, ionic liquids are preferred from the perspective of improving battery performance.

[0143] It is known that if shearing force is applied to PTFE in powder state, it is easy to fibrillate. Utilizing this fibrillated property, PTFE can be used as a binder. That is, by entanglement of fibrillated PTFE with other powder components, the powder components are bonded, and thus PTFE can play a role as a binder when the powder components are molded.

[0144] It should be noted that, even when using fibrillated PTFE as a binding agent, if fibrillation is insufficient, good performance can not be brought into play when used as an electrode mixture. Preferably, by having a fibrillated diameter (median value) (hereinafter, abbreviated as "fibrillated diameter") for the fine fibrillation processing of the fibrous structure above 20nm, fibrillated PTFE can bring into play good performance as the binding agent used for electrode mixture.

[0145] In the electrode obtained by the manufacture method of the present invention, preferably there is PTFE as a constituent element, and this PTFE has a fibrous structure with a fibril diameter (median value) of more than 20nm. In the present invention, the fibril diameter (median value) is preferably more than 20nm. That is, like this, in the electrode, there is a thin PTFE of fibril diameter, which plays the effect and flexibility of the powders that make the components of the electrode bond to each other, and is preferred from this aspect.

[0146] The fibril diameter (median value) is a value measured by the following method.

[0147] (1) Using a scanning electron microscope (S-4800, manufactured by Hitachi, Ltd.), a magnified photograph (7000 times) of the electrode mixture sheet was taken to obtain an image.

[0148] (2) Draw two lines at equal intervals horizontally on the image to divide the image into three equal parts.

[0149] (3) For all PTFE fibers located on the upper straight line, measure the diameter of each PTFE fiber at three locations, and take the average value as the diameter of the PTFE fiber. The three locations to be measured are the intersection of the PTFE fiber and the straight line, and the locations offset 0.5 μm upward and downward from the intersection. (Not including unfiberized PTFE primary particles).

[0150] (4) The above-mentioned operation (3) is performed on all PTFE fibers located on the lower straight line.

[0151] (5) Starting from the first image, move 1 mm to the right of the screen and take another photo, and measure the diameter of the PTFE fiber using the above (3) and (4). Repeat this operation until the number of measured fibers exceeds 80.

[0152] (6) The median value of the diameters of all the PTFE fibers measured above is taken as the fibril diameter.

[0153] The fibril diameter is preferably more than 15 nm, preferably more than 20 nm, more preferably more than 31 nm. If excessive fibrillation is performed, there is a tendency to lose flexibility. In addition, the upper limit is not particularly limited, and from the aspect of flexibility, for example, is preferably less than 150 nm, more preferably less than 100 nm, and particularly preferably less than 75 nm.

[0154] The method for obtaining PTFE having the above fibril diameter is not particularly limited, and an example thereof includes a method of performing the following steps:

[0155] Step (2), mixing the electrode preparation composition while applying shear force to obtain an electrode mixture;

[0156] Step (3), forming the electrode mixture obtained in the above step (2) into a block; and

[0157] Step (4) is to roll the block-shaped electrode mixture obtained in the above step (3) into a sheet.

[0158] The above-mentioned step (2) is a step of mixing the electrode preparation composition obtained by the above-mentioned step (1) while imparting shearing force to obtain an electrode mixture. It should be noted that the powder components used to prepare the electrode preparation composition can also be mixed, and shearing force can be applied while mixing to fibrillate PTFE to prepare an electrode mixture.

[0159] In this method, for example, by setting the mixing condition of the electrode manufacturing composition to 2000 rpm or less in step (2), PTFE can be fibrillated while maintaining flexibility, and by controlling the shear stress provided, the fibril diameter of PTFE can be made greater than 20 nm.

[0160] As described above, the electrode-forming composition in step (2) preferably contains a solvent content of 10% by mass or less. When the solvent content is 10% by mass or less, the drying step can be omitted, and productivity is improved, which is preferred.

[0161] Furthermore, it is also preferable to have a step (5) after the step (4) in which a greater load is applied to the obtained rolled sheet to roll it into a thinner sheet. It is also preferable to repeat the step (5).

[0162] In addition, after step (4) or step (5), the diameter of the original fibers can also be adjusted by having step (6), which is: the obtained calendered sheet is roughly crushed and then re-molded into a block shape, and calendered into a sheet shape. Step (6) is preferably repeated, for example, once or more and 12 times or less.

[0163] That is, by applying shear force, PTFE is fibrillated and entangled with powder components such as electrode active materials, thereby producing an electrode mixture. It should be noted that the production method is described below.

[0164] In the manufacture method of electrode of the present invention, the content of PTFE is generally more than 0.1 mass % in the ratio of PTFE in electrode mixture, is preferably more than 0.5 mass %, more preferably more than 1.0 mass %, in addition, is generally below 50 mass %, is preferably below 10 mass %, more preferably below 8 mass %, most preferably below 1.8 mass %.If the ratio of PTFE is too low, then can't fully keep active material, the mechanical strength deficiency of electrode makes battery performance such as cycle characteristics deteriorate.On the other hand, if the ratio of PTFE is too high, then sometimes cause the reduction of battery capacity, conductivity.

[0165] The electrode mixture of the present invention can be used as an electrode mixture for secondary batteries. In particular, the electrode mixture of the present invention is suitable for lithium ion secondary batteries.

[0166] When used in a secondary battery, the electrode mixture of the present invention is usually used in the form of a sheet.

[0167] An example of a specific method for producing an electrode mixture sheet including an electrode mixture is described below.

[0168] In the electrode manufacturing method of the present invention, the electrode mixture sheet can be obtained by a manufacturing method of an electrode mixture sheet for a secondary battery having the following steps:

[0169] Step (0), preparing a mixture containing an electrode active material and, if necessary, a conductive auxiliary agent;

[0170] Step (1), preparing a composition for electrode production containing a binder in the mixture obtained in the above step (0);

[0171] Step (2), mixing the electrode preparation composition while applying shear force to obtain an electrode mixture;

[0172] Step (3), forming the electrode mixture obtained in the above step (2) into a block; and

[0173] Step (4) is to roll the block-shaped electrode mixture obtained in the above step (3) into a sheet.

[0174] In the above-mentioned process (2), the electrode is mixed with the composition for making the electrode, and the shear force is given to the electrode active material, the binder, etc., and the electrode active material, the binder, etc. are simply mixed without a fixed shape. As a specific mixing method, a method for mixing using a W-type mixer, a V-type mixer, a drum mixer, a ribbon mixer, a conical screw mixer, a single screw mixer, a twin screw mixer, a mixing mill, a stirring mixer, a planetary mixer, etc. can be enumerated.

[0175] In the above-mentioned step (2), the mixing conditions only need to set the rotation speed and mixing time appropriately. For example, the rotation speed is preferably below 2200rpm. It is preferably above 10rpm, more preferably above 15rpm, and further preferably above 20rpm. In addition, it is preferably below 2000rpm, more preferably below 1800rpm, and further preferably in the range of 1500rpm. If it is lower than the above-mentioned range, mixing takes time and productivity is affected. In addition, if it exceeds the above-mentioned range, fibrillation is excessively performed, and it is possible to become an electrode mixture sheet with poor strength and flexibility.

[0176] In the above step (3), forming into a block shape means forming the electrode-forming composition into a single block.

[0177] Specific examples of the method for forming the block include extrusion molding, press molding, and the like.

[0178] In addition, the so-called "block-shaped" is not a particularly specific shape, as long as it is in a block-shaped state, including rod-shaped, sheet-shaped, spherical, cubic and other forms. The size of the block is preferably such that the diameter of the cross section or the smallest side is 10000 μm or more, and more preferably 20000 μm or more.

[0179] As a specific rolling method in the above step (4), there can be mentioned a method of rolling using a roll press, a flat plate press, a calender roll machine or the like.

[0180] In addition, after step (4), it is also preferred to have step (5): applying a greater load to the obtained calendered sheet to calender it into a thinner sheet. It is also preferred to repeat step (5). In this way, the calendered sheet is not thinned all at once, but is calendered little by little in stages, thereby making the softness better.

[0181] The number of times of performing step (5) is preferably 2 to 10 times, and more preferably 3 to 9 times.

[0182] As a specific calendering method, for example, the following method can be cited: two or more rollers are rotated, and a calender sheet is passed therebetween, thereby processing into a thinner sheet. Preferably, heating is performed during calendering. The lower limit of the temperature range is preferably above 40 degrees, more preferably above 50 degrees, and more preferably above 60 degrees. In addition, the upper limit is preferably below 300 degrees, more preferably below 250 degrees, and more preferably below 200 degrees. By heating, the sheet softens and can be easily calendered.

[0183] In addition, from the perspective of adjusting the diameter of the fibrils, it is also preferred to have a step (6) after the step (4) or the step (5): the rolled sheet is roughly crushed and then re-molded into a block shape, and rolled into a sheet shape. It is also preferred to repeat the step (6). The number of times of the step (6) is preferably 1 to 12 times, and more preferably 2 to 11 times.

[0184] In step (6), as a specific method for roughly crushing the rolled sheet and forming it into a block, there can be cited a method of folding the rolled sheet, a method of forming it into a rod or a film sheet, a method of forming it into a chip, etc. In the present invention, "roughly crushing" means changing the shape of the rolled sheet obtained in step (4) or step (5) into another shape in order to roll it into a sheet in the next step, and also includes the case of simply folding the rolled sheet.

[0185] In addition, step (5) may be performed after step (6), or the steps may be performed repeatedly.

[0186] Furthermore, uniaxial stretching or biaxial stretching may be performed in step (3) or (4), (5) or (6).

[0187] In addition, the fibril diameter can also be adjusted by adjusting the degree of coarse pulverization in step (6).

[0188] In the above steps (4), (5) or (6), the calendering rate is preferably 10% or more, more preferably 20% or more, and preferably 80% or less, more preferably 65% ​​or less, and more preferably 50% or less. If it is less than the above range, it takes time as the number of calendering increases, which affects productivity. In addition, if it exceeds the above range, fibrillation is excessively performed, and it is possible to form an electrode mixture sheet with poor strength and flexibility.

[0189] It should be noted that the rolling rate mentioned here refers to the reduction rate of the thickness of the sample after processing relative to the thickness before the rolling process. The sample before rolling can be a block-shaped electrode manufacturing composition, or a sheet-shaped electrode manufacturing composition. The thickness of the sample refers to the thickness of the direction in which the load is applied during rolling.

[0190] As mentioned above, PTFE powder is fibrillated by applying shearing force. And, in order to have the fibrous structure that fibrillation diameter is more than 20nm, excessive shearing stress can excessively promote fibrillation, sometimes impairs flexibility. In addition, in terms of intensity, weak shearing stress is sometimes insufficient. Therefore, when mixing or calendering, by appropriately applying shearing stress to PTFE in the above-mentioned scope to promote fibrillation, calendering resin and extend into the operation of lamellar, it is possible to have the fibrous structure that fibrillation diameter is more than 20nm.

[0191] The electrode mixture sheet of the present invention can be used as an electrode mixture sheet for a secondary battery. It can be made into either a negative electrode or a positive electrode. In particular, the electrode mixture sheet of the present invention is suitable for a lithium ion secondary battery.

[0192] (positive electrode)

[0193] In the present invention, the positive electrode is preferably composed of a current collector and an electrode mixture sheet containing the above-mentioned positive electrode active material.

[0194] Examples of the material of the positive electrode current collector include metals such as aluminum, titanium, tantalum, stainless steel, nickel, or alloys thereof, and carbon materials such as carbon cloth and carbon paper. Among them, metal materials, particularly aluminum or alloys thereof, are preferred.

[0195] As the shape of the current collector, in the case of metal materials, metal foil, metal cylinder, metal coil, metal plate, metal plate net, stamping metal, foamed metal, etc. can be enumerated, and in the case of carbon materials, carbon plate, carbon film, carbon cylinder, etc. can be enumerated. Among these, metal foil is preferred. It should be noted that metal foil can be suitably formed into a mesh.

[0196] The thickness of the metal foil is arbitrary, usually 1 μm or more, preferably 3 μm or more, more preferably 5 μm or more, and usually 1 mm or less, preferably 100 μm or less, more preferably 50 μm or less. If the metal foil is thinner than this range, the strength required as a current collector is sometimes insufficient. On the contrary, if the metal foil is thicker than this range, the handling property is sometimes impaired.

[0197] In addition, from the perspective of reducing the electrical contact resistance between the current collector and the positive electrode mixture sheet, it is also preferred that a conductive auxiliary agent is coated on the surface of the current collector. Examples of the conductive auxiliary agent include carbon or precious metals such as gold, platinum, and silver.

[0198] The ratio of the thickness of the current collector to the positive electrode mixture sheet is not particularly limited, and the value of (the thickness of the positive electrode mixture sheet on one side before the electrolyte is injected) / (the thickness of the current collector) is preferably less than 20, more preferably less than 15, and most preferably less than 10. In addition, it is preferably more than 0.5, more preferably more than 0.8, and most preferably more than 1. If it exceeds this range, the current collector sometimes generates heat caused by Joule heat during charging and discharging at high current density. If it is less than this range, the volume ratio of the current collector to the positive electrode active material increases, and the capacity of the battery sometimes decreases.

[0199] The positive electrode may be produced by a conventional method, for example, a method in which the electrode mixture sheet and the current collector are laminated with a binder and vacuum dried.

[0200] The density of the positive electrode mixture sheet is preferably 3.00 g / cm 3 More preferably, 3.10 g / cm 3 More preferably, 3.20 g / cm 3 More than 3.80 g / cm 3 Below, more preferably 3.75g / cm 3 Below, more preferably 3.70 g / cm 3 If the range is exceeded, the permeability of the electrolyte to the interface between the collector and the active material is reduced, and the charge-discharge characteristics under high current density are reduced, and sometimes high output cannot be obtained. In addition, if it is less than this range, the conductivity between the active materials is reduced, and sometimes the battery resistance increases and high output cannot be obtained.

[0201] From the perspective of high output and improved stability at high temperatures, the area of ​​the positive electrode mixture sheet is preferably larger than the outer surface area of ​​the battery case. Specifically, relative to the surface area of ​​the outer packaging of the secondary battery, the sum of the electrode mixture areas of the positive electrode is preferably 15 times or more in terms of area ratio, and more preferably 40 times or more. Regarding the outer surface area of ​​the battery case, in the case of a square shape with a bottom, it refers to the total area calculated by the length, width and thickness dimensions of the shell part filled with the power generation element except the protruding portion of the terminal. In the case of a cylindrical shape with a bottom, it refers to the geometric surface area of ​​the shell part filled with the power generation element except the protruding portion of the terminal. The sum of the electrode mixture areas of the positive electrode refers to the geometric surface area of ​​the positive electrode mixture layer facing the mixture layer containing the negative electrode active material. In a structure where a positive electrode mixture layer is formed on both sides by a collector foil, it refers to the sum of the areas calculated for each face.

[0202] The thickness of the positive electrode is not particularly limited. From the perspective of high capacity and high output, the thickness of the composite sheet after deducting the thickness of the collector is preferably 10 μm or more, more preferably 20 μm or more, as a lower limit relative to a single side of the collector. In addition, the upper limit is preferably 500 μm or less, more preferably 450 μm or less.

[0203] In addition, a positive electrode having a substance having a different composition attached to the surface of the positive electrode may also be used. Examples of the surface-attached substance include oxides such as aluminum oxide, silicon oxide, titanium oxide, zirconium oxide, magnesium oxide, calcium oxide, boron oxide, antimony oxide, and bismuth oxide; sulfates such as lithium sulfate, sodium sulfate, potassium sulfate, magnesium sulfate, calcium sulfate, and aluminum sulfate; carbonates such as lithium carbonate, calcium carbonate, and magnesium carbonate; carbon; and the like.

[0204] (negative electrode)

[0205] In the present invention, the negative electrode is preferably composed of a current collector and an electrode mixture sheet containing the above-mentioned negative electrode active material.

[0206] The material of the negative electrode current collector includes metals such as copper, nickel, titanium, tantalum, stainless steel, or alloys thereof; and carbon materials such as carbon cloth and carbon paper. Among them, metal materials are preferred, and copper, nickel, or alloys thereof are particularly preferred.

[0207] As the shape of the current collector, in the case of metal materials, metal foil, metal cylinder, metal coil, metal plate, metal plate net, stamping metal, foamed metal, etc. can be enumerated, and in the case of carbon materials, carbon plate, carbon film, carbon cylinder, etc. can be enumerated. Among these, metal foil is preferred. It should be noted that metal foil can be suitably formed into a mesh.

[0208] The thickness of the metal foil is arbitrary, usually 1 μm or more, preferably 3 μm or more, more preferably 5 μm or more, and usually 1 mm or less, preferably 100 μm or less, more preferably 50 μm or less. If the metal foil is thinner than this range, the strength required as a current collector is sometimes insufficient. On the contrary, if the metal foil is thicker than this range, the handling property is sometimes impaired.

[0209] The negative electrode may be produced by a conventional method, for example, a method in which the electrode mixture sheet and the current collector are laminated with a binder and then vacuum dried.

[0210] The density of the negative electrode mixture sheet is preferably 1.3 g / cm 3 More preferably, 1.4 g / cm 3 More preferably, 1.5 g / cm 3 More than, preferably 2.0 g / cm 3 Below, more preferably 1.9 g / cm 3 Below, more preferably 1.8 g / cm 3 If the range is exceeded, the permeability of the electrolyte to the interface between the collector and the active material is reduced, and the charge-discharge characteristics under high current density are reduced, and sometimes high output cannot be obtained. In addition, if it is less than this range, the conductivity between the active materials is reduced, and sometimes the battery resistance increases and high output cannot be obtained.

[0211] The thickness of the negative electrode is not particularly limited. From the perspective of high capacity and high output, the thickness of the composite sheet after deducting the thickness of the collector is preferably 10 μm or more, more preferably 20 μm or more, as a lower limit relative to a single side of the collector. In addition, the upper limit is preferably 500 μm or less, more preferably 450 μm or less.

[0212] (Element ratio of fluorine to carbon (F / C ratio))

[0213] The binder of the present invention preferably has an element ratio of fluorine to carbon (F / C ratio) of 0.40 to 3.00, more preferably 0.50 to 2.50. By being within such a range, an electrode with high strength and low electrode resistance can be manufactured, which is preferred from this aspect. It should be noted that elemental analysis is a value measured using a common general method. Specifically, the F / C ratio can be measured simultaneously with CHN using MICRO CORDER JM10 (manufactured by J Science Lab) under the conditions of a sample amount of 2 mg, a combustion furnace of 950°C, a reduction furnace of 550°C, a helium flow rate of 200 mL / min, and an oxygen flow rate of 15 to 25 mL / min, and the average value of the values ​​measured 4 times is obtained.

[0214] F / C ratio = average F (weight %) / average C (weight %)

[0215] (Secondary battery)

[0216] The electrode produced by the method for producing a secondary battery electrode of the present invention can be used as a positive electrode or a negative electrode in various secondary batteries. The secondary battery is a battery using a non-aqueous electrolyte, and an example thereof is a lithium ion battery.

[0217] (Electrolyte)

[0218] As the non-aqueous electrolyte solution, a non-aqueous electrolyte solution obtained by dissolving a known electrolyte salt in a known organic solvent for dissolving an electrolyte salt can be used.

[0219] There is no particular limitation on the organic solvent used to dissolve the electrolyte salt. Known hydrocarbon solvents such as propylene carbonate, ethylene carbonate, butylene carbonate, γ-butyrolactone, 1,2-dimethoxyethane, 1,2-diethoxyethane, dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate; and one or more fluorine-based solvents such as fluoroethylene carbonate, fluoroethers, and fluorinated carbonates can be used.

[0220] Examples of the electrolyte salt include LiClO 4 、LiAsF 6 , LiBF 4 、LiPF 6 、LiN(SO 2 CF 3 ) 2 、LiN(SO 2 C 2 F 5 ) 2 In terms of good cycle characteristics, LiPF is particularly preferred. 6 , LiBF 4 、LiN(SO 2 CF 3 ) 2 、LiN(SO 2 C 2 F 5 ) 2 or a combination thereof.

[0221] The concentration of the electrolyte salt needs to be 0.8 mol / L or more, and further needs to be 1.0 mol / L or more. The upper limit also depends on the organic solvent for dissolving the electrolyte salt, but is usually 1.5 mol / L.

[0222] (Battery Design)

[0223] The electrode mixture group may be any one of an electrode mixture group having a layered structure in which a separator is interposed between the positive electrode and the negative electrode, and an electrode mixture group having a structure in which the positive electrode and the negative electrode are spirally wound with the separator interposed therebetween.

[0224] (Diaphragm)

[0225] The secondary battery of the present invention preferably further includes a separator.

[0226] The material and shape of the above-mentioned diaphragm are not particularly limited as long as the electrolyte is stable and has excellent liquid retention, and a known diaphragm can be used. Among them, it is preferred to use a porous sheet or non-woven fabric-like material formed by a material that is stable to the electrolyte of the present invention or the electrolyte used in the alkali metal secondary battery of the present invention, using resin, glass fiber, inorganic material, etc., and having excellent liquid retention.

[0227] As materials for resin and glass fiber separators, polyolefins such as polyethylene and polypropylene, aromatic polyamides, PTFE, polyethersulfone, glass filter materials, etc. can be used. These materials such as polypropylene / polyethylene two-layer membranes and polypropylene / polyethylene / polypropylene three-layer membranes can be used alone or in any combination and ratio.

[0228] Among them, the separator is preferably a porous sheet or nonwoven fabric made of polyolefin such as polyethylene or polypropylene from the viewpoint of good electrolyte permeability and shutdown effect.

[0229] The thickness of the separator is arbitrary, usually 1 μm or more, preferably 5 μm or more, more preferably 8 μm or more, and usually 50 μm or less, preferably 40 μm or less, more preferably 30 μm or less. If the separator is too thin compared to the above range, the insulation and mechanical strength are sometimes reduced. In addition, if it is too thick compared to the above range, the battery performance such as rate characteristics is sometimes reduced, and the energy density of the electrolyte battery as a whole is sometimes reduced.

[0230] In addition, when a porous material such as a porous sheet or nonwoven fabric is used as a diaphragm, the porosity of the diaphragm is arbitrary, usually 20% or more, preferably 35% or more, more preferably 45% or more, and usually 90% or less, preferably 85% or less, more preferably 75% or less. If the porosity is too small compared to the above range, there is a tendency for the membrane resistance to increase and the rate characteristics to deteriorate. In addition, if it is too large compared to the above range, there is a tendency for the mechanical strength of the diaphragm to decrease and the insulation to decrease.

[0231] In addition, the average pore size of the diaphragm is also arbitrary, usually 0.5 μm or less, preferably 0.2 μm or less, and usually 0.05 μm or more. If the average pore size exceeds the above range, short circuit is likely to occur. In addition, if it is less than the above range, the membrane resistance sometimes increases and the rate characteristics decrease.

[0232] On the other hand, as inorganic materials, oxides such as aluminum oxide and silicon dioxide, nitrides such as aluminum nitride and silicon nitride, and sulfates such as barium sulfate and calcium sulfate are used, and materials in the form of particles or fibers are used.

[0233] As the form, a non-woven fabric, a woven fabric, a microporous film or other thin film-shaped material is used. In the case of a thin film, it is preferred to use a thin film with a pore size of 0.01 μm to 1 μm and a thickness of 5 μm to 50 μm. In addition to the above-mentioned independent thin film shapes, a diaphragm can also be used in which a composite porous layer containing particles of the above-mentioned inorganic substance is formed on the surface of the positive electrode and / or the negative electrode using a resin binder. For example, a porous layer can be formed on both sides of the positive electrode using fluororesin as a binder and alumina particles with a particle size of 90% less than 1 μm.

[0234] (Electrode mixture group share)

[0235] In a battery using an electrode manufactured by the method for manufacturing a secondary battery electrode of the present invention, the ratio of the volume of the electrode mixture group to the battery internal volume (hereinafter referred to as the electrode mixture group occupancy rate) is usually 40% or more, preferably 50% or more, and is usually 90% or less, preferably 80% or less.

[0236] If the electrode mixture group occupancy rate is less than the above range, the battery capacity may become smaller. In addition, if it exceeds the above range, the void space is small, the battery temperature rises, the components expand, or the vapor pressure of the liquid component of the electrolyte increases, and the internal pressure rises, which will reduce the various characteristics of the battery such as the charge and discharge repetitive performance and high temperature storage, and the gas release valve that releases the internal pressure to the outside may sometimes work.

[0237] The current collecting structure is not particularly limited, but in order to more effectively improve the charge-discharge characteristics of the high current density caused by the electrolyte, it is preferred to adopt a structure that reduces the resistance of the wiring part or the joint part. In the case of reducing the internal resistance in this way, the effect of using the electrolyte can be particularly well exerted.

[0238] When the electrode mixture group is the above-mentioned laminated structure, it is preferred to use a structure formed by bundling the metal core parts of each electrode mixture layer and welding them to the terminal. When the area of ​​a piece of electrode mixture becomes larger, since the internal resistance becomes larger, it is also preferred to set multiple terminals in the electrode mixture to reduce the resistance. When the electrode mixture group is the above-mentioned winding structure, multiple lead structures can be set in the positive electrode and the negative electrode respectively, and bundled on the terminal, thereby reducing the internal resistance.

[0239] The material of the housing is not particularly limited as long as it is a material that is stable to the electrolyte used. Specifically, metals such as nickel-plated steel, stainless steel, aluminum or aluminum alloy, magnesium alloy, or a laminated film (laminated film) of resin and aluminum foil are used. From the perspective of lightweight, it is preferred to use a metal such as aluminum or an aluminum alloy, or a laminated film.

[0240] In the case of using metal, there can be mentioned a case in which metals are welded together by laser welding, resistance welding, or ultrasonic welding to form a sealed package structure; or a case in which the above metals are used to form a riveted structure through a resin gasket. In the case of using the above laminated film, there can be mentioned a case in which a sealed package structure is formed by thermally bonding resin layers to each other. In order to improve the sealing performance, a resin different from the resin used in the laminated film can also be sandwiched between the above resin layers. In particular, in the case of forming a sealed structure by thermally bonding the resin layers through the collector terminal, since the metal is bonded to the resin, it is preferred to use a resin having a polar group or a modified resin into which a polar group is introduced as the sandwiched resin.

[0241] The secondary battery of the present invention may have any shape, for example, cylindrical, square, laminated, button, large, etc. The shape and structure of the positive electrode, negative electrode, and separator may be changed according to the shape of each battery.

[0242] Example

[0243] The present invention will be specifically described below based on examples.

[0244] In the following examples, "part" and "%" mean "part by mass" and "mass %", respectively, unless otherwise specified.

[0245] [Production example 1]

[0246] Referring to Preparation Example 2 of International Publication No. 2015-080291, a PTFE aqueous dispersion (solid content: 31.2% by mass) PTFE-A was obtained. The standard specific gravity was 2.16 as a result of measurement.

[0247] [Production example 2]

[0248] Referring to Preparation Example 3 of International Publication No. 2015-080291, a PTFE aqueous dispersion (solid content 30.9 mass %) PTFE-B was obtained. The amount of fluorinated surfactant used was 3290 ppm relative to the final PTFE yield. The standard specific gravity was 2.15 as a result of measurement.

[0249] [Production example 3]

[0250] Referring to Preparation Example 1 of International Publication No. 2012 / 086710, an aqueous dispersion of modified PTFE, PTFE-C, was obtained. The polymer concentration of the obtained aqueous dispersion was 30.1% by mass, and the average primary particle size was 0.18 μm. The standard specific gravity was measured to be 2.16.

[0251] [Production example 4]

[0252] Referring to Preparation Example 1 of International Publication No. 2012-063622, an aqueous dispersion of PTFE particles, PTFE-D, was obtained. The standard specific gravity was 2.19 as a result of measurement.

[0253] Measure 0.25g of Li-100 (acetylene black) as a conductive aid, add ultrapure water as a solvent, use a mixer to stir at 2000rpm for 3 minutes to prepare a conductive aid dispersion. Afterwards, add 4.75g of aqueous dispersion PTFE-A in terms of solid content, further add ultrapure water, and adjust the concentration of the solid content. The final amount of solvent is 45g, and then stir for 1 hour with a mixing rotor to prepare a mixed solution. Afterwards, a spray dryer (manufactured by Tokyo Physical and Chemical Instruments Co., Ltd.) is used to obtain a dry powder (inlet temperature 140°C, air volume 0.60 cubic meters / minute, flow rate 5.5g / minute). Then vacuum drying (100°C, 8 hours) is performed to obtain a binder 1.

[0254] As shown in Table 1, binders 2 to 11 were obtained by changing the type and amount of the PTFE aqueous dispersion, the type and amount of the conductive additive, and the amount of the solvent.

[0255] The water content of adhesives 1 to 11 was measured and found to be 250 PPM or less for all of them.

[0256] [Table 1]

[0257]

[0258] [Production example 5]

[0259] The aqueous dispersion PTFE-D obtained in Preparation Example 4 was diluted to a solid content concentration of 15%, and stirred quietly in a container equipped with a stirrer in the presence of nitric acid to coagulate the PTFE. The coagulated PTFE was separated and dried at 160° C. for 18 hours to obtain a powdery PTFE-E containing no conductive additive.

[0260] (Example 1)

[0261] <Production of positive electrode mixture sheet>

[0262] While adding Li(Ni 0.6 Mn 0.2 Co 0.2 ) 2 (abbreviation: NMC622) and the amount of conductive aid contained in the binder to be added later, while weighing Li-100 as a conductive aid, stirring at 1500 rpm for 10 minutes using a stirrer to obtain a mixture. Add the prepared binder 1 to the container containing the mixture, stir at 40 rpm for 2 hours using a kneader to obtain a mixed powder composition. The composition is positive electrode active material: PTFE: total conductive aid = 95.5:2:2.5 in terms of mass ratio.

[0263] The obtained mixed powder composition is passed through parallel metal rollers for multiple times and rolled to produce a self-supporting electrode composite sheet. The temperature of the metal roller is set to 80°C. After that, the rolled sheet just obtained is folded in half and roughly crushed, and after being formed into a block again, it is rolled into a sheet using a metal roller on a hot plate heated to 80°C to promote fibrillation, and the above process is repeated 4 times. After that, it is further rolled to obtain a positive electrode composite sheet with a thickness of about 500μm. Furthermore, the positive electrode composite sheet is cut into 5cm×5cm and put into a roller press heated to 80°C for rolling. In order to further promote fibrillation, a load of 2kN is repeatedly applied to adjust the thickness. The gap is adjusted so that the thickness of the final positive electrode composite layer is 90μm and the density is 3.20g / cc to obtain a positive electrode composite sheet.

[0264] Each test was performed by the following method.

[0265] [Strength measurement]

[0266] A tensile tester (Autograph AGS-X series AGS-100NX manufactured by Shimadzu Corporation) was used to measure the strength of each sample using a 4 mm wide strip of positive electrode mixture sheet under the condition of 100 mm / min. The distance between the chucks was set to 30 mm. Displacement was given until fracture, and the maximum stress of the measurement result was used as the strength of each sample. Comparative Example 1 was set to 100 for comparison.

[0267] [Electrode resistance measurement]

[0268] The positive electrode mixture sheet was cut into a square of 5.0 cm in width and 10 cm in length to prepare a test piece. The four-terminal resistance of the positive electrode active material layer was measured using a resistivity meter Loresta GP (manufactured by Mitsubishi Chemical Corporation) in accordance with JIS K7194; 1994. The smaller the resistance value, the better the battery characteristics.

[0269] A: less than 20Ωcm

[0270] B: 20Ωcm~less than 50Ωcm

[0271] C: 50Ωcm~less than 100Ωcm

[0272] D: 100Ωcm~less than 200Ωcm

[0273] E: 200Ωcm~or more

[0274] (Examples 2 and 3)

[0275] A positive electrode mixture sheet was obtained in the same manner as in Example 1 except that a binder having a composition shown in Table 1 was used.

[0276] (Examples 4 to 7)

[0277] A positive electrode mixture sheet was obtained in the same manner as in Example 1 except that the conductive auxiliary agent mixed with NMC622 in the mixer was changed to Super-P Li (furnace black) and a binder with the composition shown in Table 1 was used.

[0278] (Examples 8 and 9)

[0279] As the positive electrode active material, Li(Ni 0.8 Mn 0.1 Co 0.1 ) 2 (abbreviation: NMC811), Li-100 as a conductive aid, and binder 8. The mixed powder composition was positive electrode active material: PTFE: FT7000 (multi-walled carbon nanotubes with an average diameter of 7nm to 11nm and a length of 5μm to 20μm): Li-100 = 95.5:2:0.04:2.46 in terms of mass ratio. A positive electrode mixture sheet was obtained in the same manner as in Example 1 except for this. Example 9 was also carried out in the same manner.

[0280] (Example 10)

[0281] NMC811 was used as a positive electrode active material, Li-100 was used as a conductive additive, and a binder 10 was used. The mixed powder composition had a mass ratio of positive electrode active material: PTFE: FT7000: Li-100 = 95.5: 2: 0.11: 2.34. A positive electrode mixture sheet was obtained in the same manner as in Example 1 except for the above.

[0282] (Example 11)

[0283] A positive electrode mixture sheet was obtained in the same manner as in Example 1 except that the conductive additive mixed with NMC622 in the mixer was changed to carbon ECP (Ketjen Black) and the binder with the composition shown in Table 1 was used.

[0284] (Example 12)

[0285] As the positive electrode active material, NMC811 and binder 5 were used. The mixed powder composition had a mass ratio of positive electrode active material:PTFE:total conductive additive=96:1.5:2.5. A positive electrode mixture sheet was obtained in the same manner as in Example 1 except for the above.

[0286] <Production of positive electrode>

[0287] The positive electrode mixture sheet is bonded to a 20 μm aluminum foil. The adhesive is a slurry in which polyvinylidene fluoride (PVDF) is dissolved in N-methylpyrrolidone (NMP) and carbon nanotubes (CNT) are dispersed. The above adhesive is applied to the aluminum foil, and the prepared sheet-shaped positive electrode mixture is placed in a manner that does not generate bubbles. It is vacuum dried at 120°C for 30 minutes to prepare a positive electrode sheet that is integrated with the collector.

[0288] <Preparation of electrolyte>

[0289] As an organic solvent, a mixed solvent of ethylene carbonate (EC) and ethyl methyl carbonate (EMC) (EC:EMC=30:70 (volume ratio)) was measured in a sample bottle, and 1% by mass of fluoroethylene carbonate (FEC) and vinylene carbonate (VC) were dissolved therein to prepare an electrolyte solution, and the LiPF 6 The salt concentration was 1.0 mol / L, and the mixture was mixed at 23° C. to obtain an electrolyte solution.

[0290] <Battery production>

[0291] A button cell is made using the positive electrode sheet and polyethylene separator made as above, and Li metal as the negative electrode. In detail, in a drying room, the separator is sandwiched between the positive electrode and the negative electrode to make an electrode body battery. The electrode body battery is housed in a battery case (CR2032 type button cell component) composed of a stainless steel container. An electrolyte is injected into the battery case. The battery case is sealed with a riveting machine to obtain a non-aqueous electrolyte lithium-ion secondary battery of the embodiment.

[0292] [Initial discharge capacity test]

[0293] The lithium ion secondary battery manufactured as described above was charged at 25°C with a constant current-constant voltage charge (hereinafter referred to as CC / CV charge) equivalent to 0.5C to 4.3V (0.1C cut-off), and then discharged at a constant current of 0.5C to 3V. This was regarded as one cycle, and the initial discharge capacity was calculated from the discharge capacity of the third cycle.

[0294] The initial capacity of the reference example is set to 100 for comparison.

[0295] (Comparative Example 1)

[0296] A nonaqueous electrolyte lithium ion secondary battery was obtained in the same manner as in Example 1 except that powdery PTFE-E containing no conductive auxiliary agent was used.

[0297] (Comparative Example 2)

[0298] A nonaqueous electrolyte lithium ion secondary battery was obtained in the same manner as in Example 1 except that powdery PTFE-E containing no conductive additive was used and the conductive additive was changed to Super-P Li.

[0299] (Reference example)

[0300] Weigh NMC811 as the positive electrode active material, Li-100 and FT7000 as the conductive aid, and stir them at 1500 rpm for 10 minutes using a stirrer to obtain a mixture. Add the prepared powdered PTFE-E to the container containing the mixture, and stir it at 40 rpm using a mixer for 2 hours to obtain a mixed powder composition. The composition is positive electrode active material: PTFE: FT7000: Li-100 = 95.5:2:0.04:2.46 in terms of mass ratio. Prepare an electrode mixture sheet according to the same steps as in Example 8 to obtain a non-aqueous electrolyte lithium-ion secondary battery.

[0301] (Comparative Example 3)

[0302] Weigh the Li(Ni 0.8 Mn 0.1 Co 0.1 ) 2(NMC811), and Li-100 as a conductive aid, are stirred at 2000 rpm for 10 minutes using a stirrer to obtain a mixture. The prepared aqueous dispersion PTFE-D is added to the container containing the mixture, and stirred at 40 rpm for 2 hours using a mixer to obtain a mixed powder composition. The composition is positive electrode active material: PTFE: conductive aid = 95.5:2:2.5 in terms of mass ratio. Since agglomerates were observed in the dispersion before drying, spray drying was not performed, and drying was performed at 110°C for 1 hour using a hot plate. Further vacuum drying (100°C, 8 hours) was performed to obtain a mixed powder composition. An electrode mixture sheet was prepared according to the same steps as in Example 8 to obtain a non-aqueous electrolyte lithium-ion secondary battery.

[0303] (Comparative Example 4)

[0304] A nonaqueous electrolyte lithium ion secondary battery was obtained in the same manner as in Example 12 except that powdery PTFE-E containing no conductive aid was used.

[0305] [Table 2]

[0306] Binder Tensile Strength Electrode resistance Comparative Example 1 PTFE-E 100 E Example 1 Binder 1 120 D Example 2 Binder 2 106 A Example 3 Binder 3 110 B Comparative Example 2 PTFE-E 88 E Example 4 Binder 4 106 C Example 5 Binder 5 128 C Example 6 Binder 6 110 C Example 7 Binder 7 102 C Embodiment 11 Binder 11 115 A

[0307] [Table 3]

[0308] Tensile Strength Electrode resistance Initial capacity Reference example 70 C 100 Comparative Example 3 55 E 84 Comparative Example 4 85 E 99 Example 8 105 A 102 Example 9 110 A 102 Example 10 120 A 103 Example 12 100 B 105

[0309] The fibril diameters of Examples 1 and 3 were measured and found to have median values ​​of 40 nm and 31 nm, respectively.

[0310] The fibril diameters of Examples 4 and 5 were measured and found to have median values ​​of 33 nm and 43 nm, respectively.

[0311] The fibril diameters of Examples 9, 10, 11, and 12 were measured, and the median values ​​of the fibril diameters were 51 nm, 67 nm, 40 nm, and 32 nm, respectively.

[0312] It can be seen from Comparative Example 1 and Examples 1 to 3 that electrodes having high tensile strength and low electrical resistance can be produced.

[0313] In addition, the preferred ranges of the conductive material and PTFE were found from Comparative Example 2 and Examples 4 to 7. In addition, it was found from Comparative Example 3 and Example 8 that the battery characteristics can be improved by using a binder as a powder that does not contain an electrode active material. In Example 12, the amount of binder can be reduced and the battery capacity can be increased.

[0314] Industrial Applicability

[0315] The method for producing a secondary battery electrode using the nonaqueous electrolyte solution of the present invention can be used to produce an electrode used in a battery such as a lithium ion secondary battery.

Claims

1. A method for producing an electrode for a secondary battery using a non-aqueous electrolyte, characterized in that: have: Step (1), using a binder which is a powder composed of a composition containing a polytetrafluoroethylene resin and a conductive aid as essential components and does not contain an active material, to prepare a composition for electrode production in the form of a powder; and Step (2), mixing the electrode preparation composition while applying shear force to obtain an electrode mixture, The step (2) is performed under the condition that the amount of solvent contained in the electrode-forming composition is 10% by mass or less.

2. The method for producing a secondary battery electrode according to claim 1, wherein: The content of polytetrafluoroethylene resin in the electrode mixture is 1.8% by mass or less.

3. The method for producing a secondary battery electrode according to claim 1 or 2, wherein: The moisture content of the binder is 1000 ppm or less.

4. The method for producing a secondary battery electrode according to any one of claims 1 to 3, wherein: The binder is produced by a production method including a step (A) of mixing a polytetrafluoroethylene resin and a conductive additive in the presence of a liquid medium.

5. The method for producing a secondary battery electrode according to claim 4, wherein: The liquid medium is water.

6. The method for producing a secondary battery electrode according to claim 4 or 5, wherein: The binder is obtained by a production method having a step (B) of drying the composition obtained in the step (A) by spray drying.

7. The method for producing a secondary battery electrode according to any one of claims 1 to 6, wherein: The standard specific gravity of the polytetrafluoroethylene resin is 2.130 to 2.

200.

8. The method for producing a secondary battery electrode according to any one of claims 1 to 7, wherein: The electrode manufacturing composition contains a positive electrode active material.

9. The method for producing a secondary battery electrode according to any one of claims 1 to 8, wherein: The secondary battery is a lithium ion secondary battery.

10. The method for producing a secondary battery electrode according to any one of claims 1 to 9, wherein: The polytetrafluoroethylene resin has a fibrous structure in which the fibril diameter, that is, the median value, in the secondary battery electrode is 20 nm or more.

11. The method for producing a secondary battery electrode according to any one of claims 1 to 10, wherein: The binder has an element ratio of fluorine to carbon, that is, a F / C ratio, of 0.4 to 3.0 as measured by elemental analysis.

12. A binder for secondary battery electrodes using a non-aqueous electrolyte, characterized in that: The invention is a powder composed of a composition having a polytetrafluoroethylene resin and a conductive auxiliary agent as essential components and containing no electrode active material, and contains the polytetrafluoroethylene resin and the conductive auxiliary agent in a weight ratio of 90:10 to 65:

35. 13 . The binder for secondary battery electrodes according to claim 12 , wherein the water content of the binder is 1000 ppm or less.

14. The binder for secondary battery electrodes according to claim 12 or 13, wherein The element ratio of fluorine to carbon, that is, the F / C ratio measured by elemental analysis is 0.4 or more and 3.0 or less.

15. A binder for secondary battery electrodes using a non-aqueous electrolyte, characterized in that: Contains a mixed powder of polytetrafluoroethylene resin and Ketjen black and / or carbon nanotubes.

16. A composition for electrode preparation, characterized in that: Contains the binder for secondary battery electrodes according to claim 15.

17. An electrode mixture, characterized in that: Contains the binder for secondary battery electrodes according to claim 15.

18. An electrode, characterized in that: An electrode mixture according to claim 17.

Citation Information

Patent Citations

  • Production of powdery carbon black-ptfe uniform mixture

    JP1994316784A

  • Concentrated Fluoropolymer Dispersion

    JP2005527652A

  • Method for producing composite particle for electrode of electrochemical element

    JP2008140809A

  • Dry electrode for energy storage device and its manufacturing method

    JP2017517862A

  • Positive electrode active material for nonaqueous electrolyte secondary battery, and nonaqueous electrolyte secondary battery

    JP2020115485A